Wolbachia Inhibits Binding of Dengue and Zika Viruses to Mosquito Cells - Lu, Peng; Sun, Qiang; Fu, Ping; Li, Kuibiao; Liang, Xiao; Xi, Zhiyong (Frontiers in Microbiology, 2020)
As traditional approaches to the control of dengue and Zika are insufficient, significant efforts have been made to develop utilization of the endosymbiotic bacterium Wolbachia to reduce the ability of mosquitoes to transmit pathogens. Although Wolbachia is known to inhibit flaviviruses in mosquitoes, including dengue virus (DENV) and Zika virus (ZIKV), it remains unclear how the endosymbiont interferes with viral replication cycle. In this study, we have carried out viral binding assays to investigate the impact of the Wolbachia strain wAlbB on the attachment of DENV serotype 2 (DENV-2) and ZIKV to Aedes aegypti Aag-2 cells. RNA interference (RNAi) was used to silence a variety of putative mosquito receptors of DENV that were differentially regulated by wAlbB in Aag-2 cells, in order to identify host factors involved in the inhibition of viral binding. Our results showed that, in addition to suppression of viral replication, Wolbachia strongly inhibited binding of both DENV-2 and ZIKV to Aag-2 cells. Moreover, the expression of two putative mosquito DENV receptors – dystroglycan and tubulin – was downregulated by wAlbB, and their knock-down resulted in the inhibition of DENV-2 binding to Aag-2 cells. These results will aid in understanding the Wolbachia-DENV interactions in mosquito and the development of novel control strategies for mosquito-borne diseases.